(untitled) (EAAE Annual Conference Proceedings, 2023)
The NEB recognizes the innovative potential of architecture in relation to our society’s need, digging into questions on the position of the discipline of architecture, its practice and its education. Questions that have been looked into within the Erasmus+ “Architecture’s Afterlife” research project. The study investigating the diverse trajectories of architecture alumni, clearly showed that the competencies acquired in architectural education set up a professional modus operandi and identity that can take many forms.